Harbor seal pup dispersal and individual morphology, hematology, and contaminant factors affecting survival - Greig, Denise J.; Gulland, Frances M.D.; Harvey, James T.; Lonergan, Mike; Hall, Ailsa J. (Marine Mammal Science, 2019)
Understanding the factors affecting individual harbor seal (Phoca vitulina) survival is essential for determining population level health risks. We estimated postweaning dispersal, and modeled the effects of morphology, hematology, and blubber contaminants on the survival of recently weaned harbor seal pups using a mark recapture framework. We deployed satellite transmitters on apparently healthy pups captured in San Francisco Bay (SFB, n = 19) and Tomales Bay (TB, n = 7), and pups released after rehabilitation that stranded along the central California coast preweaning (n = 21). Dispersal distances were further than previously reported for harbor seal pups (maximum = 802 km) which has implications for understanding risks to this vulnerable age class. We found differences in body condition, serum immunoglobulin and thyroxine (T4) concentrations, white blood cell count, and blubber organohalogen contamination (OH) among the three groups. Overall, increased T4, decreased OH, and increased mass were associated with greater survival probabilities; whereas, among stranded seals, greater mass gain, shorter time in rehabilitation, and admission to rehabilitation earlier in the season were associated with greater survival probabilities. Attention to these latter factors may improve the success of rehabilitation efforts. For wild pups, reduction of legacy contaminants and direct causes of mortality, such as ship strike, may enhance pup survival.